Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.558
|View full text |Cite
|
Sign up to set email alerts
|

Grounded Adaptation for Zero-shot Executable Semantic Parsing

Abstract: We propose Grounded Adaptation for Zeroshot Executable Semantic Parsing (GAZP) to adapt an existing semantic parser to new environments (e.g. new database schemas). GAZP combines a forward semantic parser with a backward utterance generator to synthesize data (e.g. utterances and SQL queries) in the new environment, then selects cycleconsistent examples to adapt the parser. Unlike data-augmentation, which typically synthesizes unverified examples in the training environment, GAZP synthesizes examples in the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 14 publications
0
52
0
1
Order By: Relevance
“…Base Parser + BERT-base 66.8 63.3 Base Parser + BERT-base + DG-MAML 68.9 65.2 With BERT-large: RYANSQL + BERT-large (Choi et al, 2020) 70.6 60.6 RAT-SQL + BERT-large 69.7 65.6 Execution Accuracy GAZP + Distil-BERT (Zhong et al, 2020) 59.…”
Section: Our Modelsmentioning
confidence: 99%
“…Base Parser + BERT-base 66.8 63.3 Base Parser + BERT-base + DG-MAML 68.9 65.2 With BERT-large: RYANSQL + BERT-large (Choi et al, 2020) 70.6 60.6 RAT-SQL + BERT-large 69.7 65.6 Execution Accuracy GAZP + Distil-BERT (Zhong et al, 2020) 59.…”
Section: Our Modelsmentioning
confidence: 99%
“…EditSQL , IGSQL (Cai and Wan, 2020) and R 2 SQL (Hui et al) consider the dialogue context during translating the utterance into SQL query. GAZP (Zhong et al, 2020) proposes a zero-shot method to adapt an existing semantic parser to new domains. PIIA proposes a human-in-loop method to enhance Textto-SQL performance.…”
Section: Related Workmentioning
confidence: 99%
“…Open Domain Question Answering ODQA has been extensively studied recently including extractive models (Chen et al, 2017;Clark and Gardner, 2018;Wang et al, 2019;Min et al, 2019;Yang et al, 2019) that predict spans from evidence passages, and generative models Lewis et al, 2020;Izacard and Grave, 2020) that directly generate the answers. Wang et al (2018b,c); Nogueira and Cho (2019) proposed to rerank the retrieved passages to get higher top-n recall.…”
Section: Related Workmentioning
confidence: 99%
“…Wang et al (2018b,c); Nogueira and Cho (2019) proposed to rerank the retrieved passages to get higher top-n recall. (Zhong et al, 2017), Spider and CoSQL being introduced, many works have shown promising progress on these dataset He et al, 2019;Hwang et al, 2019;Min et al, 2019;Choi et al, 2020;Lyu et al, 2020;Zhong et al, 2020;Shi et al, 2020). Another line of work proposes to reason over tables without generating logical forms (Neelakantan et al, 2015;Lu et al, 2016;Herzig et al, 2020;Yin et al, 2020).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation